Flouting maxim analysis performed by the characters in escape room movie - Wiraningsih, Ni Luh Ayu; Utami, Ni Made Verayanti; Juniartha, I Wayan (Institut Pariwisata dan Bisnis Internasional, 2020)
This study aims to find out the types of flouting maxims and to know what the most dominant types of flouting maxims performed by the characters in the Escape Room movie is. The researcher used the theory proposed by Grice in his book Logic in Conversation (1975) to analyze the types of flouting maxims in the Escape Room movie. The method that used in this research is descriptive qualitative research. Through the findings of the analysis, there were 24 data found. Those are: Flouting Maxim of Quantity 8 data (33%), Flouting Maxim of Quality and Flouting Maxim of Relevance rarely appeared with same frequently 6 data (25%) and Flouting Maxim of Manner 4 data (17%). From those forms, Flouting Maxim of Quantity has the highest occurrences used among others.